SPECIFICATIONS AND PECULIARITIES OF ACCENT VARIETIES IN ENGLISH-SPEAKING COUNTRIES: A COMPARATIVE STUDY OF NEW ZEALAND AND AUSTRALIAN PRONUNCIATION (World Bulletin of Social Sciences, 2026)
This article examines the specifications and peculiarities of accent varieties in English-speaking countries with a particular focus on New Zealand English and Australian English pronunciation. The relevance of the study is determined by the increasing role of World Englishes in international communication, language teaching, intercultural interaction, and pronunciation awareness. Although New Zealand and Australian English are geographically and historically close varieties, they demonstrate important phonetic, phonological, and sociolinguistic differences. The study applies a qualitative comparative method based on secondary analysis of academic literature, phonological descriptions, and sociolinguistic evidence. The results show that both varieties are generally non-rhotic and historically connected with British English, but they differ significantly in vowel realization, diphthong quality, prosodic patterns, and identity-marking functions. New Zealand English is especially characterized by the centralization of KIT, raising of TRAP and DRESS, possible NEAR/SQUARE merger, and frequent use of High Rising Terminal intonation. Australian English is distinguished by a sociostylistic broadness continuum, recognizable diphthongal patterns, and relatively strong national identity marking. The article concludes that comparative accent analysis is important not only for linguistic theory, but also for English language teaching, listening comprehension, and intercultural competence
Keywords: New Zealand English; Australian English; accent varieties; pronunciation